GLYCOSAMINOGLICANS DISTRIBUTION IN THE RATS’ MAJOR SALIVARY GLANDS DURING EARLY POSTNATAL PERIOD AFTER ANTENATAL ANTIGEN ACTION - Syrtsov, V.; Maslova, I. (World of Medicine and Biology, 2014)
Purpose - to determine the features of glycoproteins’ distribution in the structures of rats’ major salivary glands in early postnatal period after intrauterine antigen action. In newborn animals receiving antigen in the antenatal period, in the cells’ cytoplasm and extracellular matrix indicate the accumulation’ increase of Alcian blue stain - positive compounds retained until the 11th and offset at the 45th day of postnatal life. The detected changes in the major salivary glands cells’ are the basis for the development of inflammatory and dystrophic processes and can lead to the functional violations formation’ hereinafter.
Keywords: major salivary glands; intrauterine antigenic action; glycosaminoglycans; rats